1996
DOI: 10.1152/jappl.1996.80.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of phosphocreatine and aerobic metabolism to energy supply during repeated sprint exercise

Abstract: This study examined the contribution of phosphocreatine (PCr) and aerobic metabolism during repeated bouts of sprint exercise. Eight male subjects performed two cycle ergometer sprints separated by 4 min of recovery during two separate main trials. Sprint 1 lasted 30 s during both main trials, whereas sprint 2 lasted either 10 or 30 s. Muscle biopsies were obtained at rest, immediately after the first 30-s sprint, after 3.8 min of recovery, and after the second 10- and 30-s sprints. At the end of sprint 1, PCr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

50
444
8
34

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(536 citation statements)
references
References 23 publications
50
444
8
34
Order By: Relevance
“…These data are consistent with the previous finding that aerobic mechanisms contribute significant amounts of energy after the first bout (Bogdanis et al 1996) and therefore an enhanced oxidative capacity would be an advantage during repeated sprint activities [8]. In addition, if endurance trained individuals are capable of faster lactate clearance (Bassett et al 1991); there should be some advantage because of an attenuated decrement in force in successive bouts [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with the previous finding that aerobic mechanisms contribute significant amounts of energy after the first bout (Bogdanis et al 1996) and therefore an enhanced oxidative capacity would be an advantage during repeated sprint activities [8]. In addition, if endurance trained individuals are capable of faster lactate clearance (Bassett et al 1991); there should be some advantage because of an attenuated decrement in force in successive bouts [13].…”
Section: Discussionsupporting
confidence: 91%
“…In handball repeated sprint occur during a game were the players ran without fatigue. This clearly shows that repeated sprint require a greater aerobic fitness component with each successive sprint bouts [8][9]. Previous studies have concluded the aerobic metabolic pathways contribute an increasingly larger portion of ATP when high intensity bouts are repeated in succession [10-11-12].…”
Section: Discussionmentioning
confidence: 65%
“…Glycolytic and aerobic sources have been shown to contribute to the energy required during a Wingate test after the first 5s of exercise (Smith & Hill, 1991). Aerobic sources have been shown to provide some of the energy for repeated sprints performed on cycle ergometer equipment (Bogdanis et al, 1996). Scaling the results of the current study up from the 15 minute observation period used to 90 minutes suggests that the average outfield player performs 18 bursts of 10 s or more that may derive energy from both aerobic and anaerobic sources.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to these rather low estimates, 5 studies that used the accumulated oxygen deficit to quantify energy supply reported values between 23 to 33% for 30 seconds of maximal, exhaustive exercise. [26,62,[66][67][68] In line with these estimates, Bogdanis et al, [69] using direct muscle measures, reported a 29% aerobic contribution. Interestingly, when a second maximal 30-second sprint was performed after 4 minutes of passive recovery, the estimated aerobic contribution increased to 44%.…”
Section: Aerobic Energy Supplymentioning
confidence: 82%